Factors Affecting Disability Employment Opportunities in the Labor Market in West Sumatra - Zulkarnain, Rizky Husna Amalia; Satrianto, Alpon (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
People with disabilities frequently encounter discrimination, particularly in gaining employment, despite having the same rights, roles, and responsibilities as the general population. This study examines the factors affecting employment opportunities for individuals with disabilities in West Sumatra in 2022, using data from SAKERNAS 2022. The analysis focuses on variables such as gender, age, marital status, education, and residential classification. The research utilizes logistic regression analysis to explore these factors. The results reveal that age has a positive influence on employment opportunities, whereas gender, marital status, education, and residential classification have significant negative effects on the employment prospects of individuals with disabilities in West Sumatra.